Stromal Fibroblasts in Tertiary Lymphoid Structures: A Novel Target in Chronic Inflammation - Barone, Francesca; Gardner, David H.; Nayar, Saba; Steinthal, Nathalie; Buckley, Christopher D.; Luther, Sanjiv A. (Frontiers in Immunology, 2016)
Tertiary lymphoid structures (TLS) are organized aggregates of lymphocytes, myeloid and stromal cells that provide ectopic hubs for acquired immune responses. TLS share phenotypical and functional features with secondary lymphoid organs (SLO); however, they require persistent inflammatory signals to arise and are often observed at target sites of autoimmune diseases, chronic infection, cancer and organ transplantation. Over the past 10 years, important progress has been made in our understanding of the role of stromal fibroblasts in SLO development, organization and function. A complex and stereotyped series of events regulates fibroblast differentiation from embryonic life in SLOs, to lymphoid organ architecture observed in adults. In contrast, TLS associated fibroblasts differentiate from post-natal, locally activated mesenchyme, predominantly in settings of inflammation and persistent antigen presentation. Therefore, there are critical differences in the cellular and molecular requirements that regulate SLO versus TLS development that ultimately impact on stromal and hematopoietic cell function. These differences may contribute to the pathogenic nature of TLS in the context of chronic inflammation and malignant transformation and offer a window of opportunity for therapeutic interventions in TLS associated pathologies.